Is Volunteering Rewarding in Itself? Evidence from a Natural Experiment - Stephan Meier; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Volunteering constitutes one of the most important pro-social activities. Following Adam Smith, helping others is the way to higher individual well-being. This view contrasts with the selfish utility maximizer who avoids costs from helping others. The two rival views are studied empirically. We find robust evidence that volunteers are more satisfied with their life than non-volunteers. Causality is addressed taking advantage of a natural experiment: the collapse of East Germany and its infrastructure of volunteering. People who accidentally lost their opportunities for volunteering are compared to people who experienced no change in their volunteer status.
Keywords: D64; I31; J22; Z13; 330; happiness; pro-social behavior; subjective well-being; volunteering